V-doped SnO2 composite material as well as synthesis method and application thereof

Synthesis of V-doped SnO2 composite materials by solvent thermal method solves the problems of low capacity and poor cycle stability of the negative electrode materials of traditional lithium-ion batteries, and achieves electrochemical performance with high capacity retention and good rate performance.

CN119528212APending Publication Date: 2025-02-28HUBEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411696609.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The negative electrode material of traditional lithium-ion batteries has low theoretical capacity, which is difficult to meet the needs of high energy storage equipment. At the same time, SnO2 expands severely during the cycle, resulting in cracking of the electrode material and degrading electrochemical properties.

Method used

The V-doped SnO2 composite material was synthesized by solvothermal method. By reacting VO2 with stannous salt in anhydrous ethanol, V-doped SnO2 composite material was formed, which was used as the negative electrode material for lithium-ion batteries.

Benefits of technology

V-doped SnO2 composites exhibit excellent electrochemical properties in lithium-ion batteries, including good cycling stability and rate performance, significantly improving capacity retention and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528212A_ABST
    Figure CN119528212A_ABST
Patent Text Reader

Abstract

The invention discloses a V-doped SnO2 composite material and a synthesis method and application thereof, and belongs to the technical field of composite material synthesis and new energy. The V-doped SnO2 composite material is successfully synthesized by taking VO2 and stannous salt as raw materials and adopting a typical solvothermal method. Different characterization technologies such as XRD, XPS and SEM are adopted to research the structure and morphology of the prepared sample. Meanwhile, the electrochemical performance of the prepared sample is tested by utilizing a battery comprehensive test system. The electrochemical reaction mechanism is analyzed by adopting cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). Experimental results show that in all samples, a proper amount of V-doped SnO2 sample (VS-2) has the best electrochemical performance and has the best cycling stability and rate capability, and the research also provides a possible reason for the V-doped SnO2 sample (VS-2). A proper V-doped SnO2 sample (VS-2) is a promising lithium ion battery negative electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite material synthesis and new energy, and specifically relates to a V-doped SnO2 composite material and a synthesis method and application thereof. Background Art

[0002] As environmental problems such as the greenhouse effect and air pollution become increasingly serious, humans have put forward higher requirements for clean, environmentally friendly, and green new energy materials. Lithium-ion batteries have the advantages of high energy density, long cycle life, and no memory effect, and are considered to be the most promising energy storage device. At present, it has been widely used in portable electronic devices such as mobile phones and laptops. With the rapid development of electric vehicles and hybrid electric vehicles, lithium-ion batteries are also considered to be the most ideal automotive energy storage devices. However, the rapid development of electric vehicles has put forward higher requirements on lithium-ion batteries, and there is an urgent need for battery materials with longer cycle life, larger capacity, better charge and discharge rate performance, and lower cost. The theoretical capacity of traditional negative electrode material graphite is low (372mAh g -1 ), which is difficult to meet the needs of high energy storage devices. People are eager to find suitable negative electrode materials to replace traditional graphite, such as metal oxides, nitrides, sulfides, silicon, etc.

[0003] Among the above materials, SnO2 has a high theoretical specific capacity (1494 mAh g -1 ), low lithium insertion potential, abundant mineral resources, low cost, environmental protection and non-toxicity, and is considered to be one of the most promising positive electrode materials. However, like the oxide of Si, another member of the IVA group, SnO2 also faces a huge volume expansion (about 250%) during the cycle. This can easily cause the electrode material to crack and peel off from the current collector, ultimately leading to a decrease in electrochemical performance. Therefore, when SnO2 is used as the negative electrode material, the specific capacity of the first cycle is high, but it decays quickly and the cycle stability is poor.

[0004] Based on the above reasons, this application is filed. Summary of the invention

[0005] Based on the above reasons, in view of the problems or defects in the prior art, the purpose of the present invention is to provide a V-doped SnO2 composite material and a synthesis method and application thereof, so as to solve or at least partially solve the above technical defects in the prior art.

[0006] In order to achieve one of the above purposes of the present invention, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a V-doped SnO2 composite material, the method specifically comprising the following steps:

[0008] The stannous salt is dissolved in anhydrous ethanol, and then vanadium dioxide (VO2) is added according to a proportion and mixed; the obtained mixed reaction liquid is reacted at room temperature under stirring conditions for 1 hour; after the reaction is completed, the reaction product is collected, washed and dried to obtain the V-doped SnO2 composite material.

[0009] In some embodiments, the stannous salt is stannous chloride or stannous sulfate.

[0010] In some embodiments, the ratio of the stannous salt to anhydrous ethanol is 1 mmol:30 mL.

[0011] In some embodiments, the molar ratio of vanadium dioxide to stannous salt is (0.5-2):1, preferably 1:1.

[0012] In some embodiments, the vanadium dioxide is synthesized by a hydrothermal method, and the specific steps are as follows:

[0013] Oxalic acid and ammonium metavanadate are dissolved in deionized water in turn according to the ratio, and then the obtained yellow solution is transferred to a high-pressure reactor, heated to 180° C. and reacted at a constant temperature for 48 hours; after the reaction is completed, the product is cooled to room temperature, centrifuged to separate the precipitate, washed, and dried to obtain the vanadium dioxide.

[0014] In some embodiments, the molar ratio of oxalic acid to ammonium metavanadate is 1:1.

[0015] In some embodiments, the ratio of ammonium metavanadate to deionized water is 5 mmol:30 mL.

[0016] The second object of the present invention is to provide a V-doped SnO2 composite material prepared by the method described above.

[0017] The third object of the present invention is to provide the use of the V-doped SnO2 composite material prepared by the above method as a negative electrode active material in a lithium ion battery.

[0018] A lithium ion battery comprises a positive electrode, a negative electrode, a separator and an electrolyte, wherein the active material used in the negative electrode is a V-doped SnO2 composite material prepared by the method described above.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention uses VO2 and stannous salt as raw materials and adopts a typical solvothermal method to successfully synthesize V-doped SnO2 composite materials. The structure and morphology of the prepared samples were studied by different characterization techniques such as XRD, XPS and SEM. At the same time, the electrochemical properties of the prepared samples were tested by a battery comprehensive test system. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were used to analyze the electrochemical reaction mechanism. The experimental results show that among all the samples, the electrochemical performance of the SnO2 sample (VS-2) doped with an appropriate amount of V has the best cycle stability and rate performance, and this study also proposes possible reasons for this. The appropriate V-doped SnO2 sample (VS-2) is a promising negative electrode material for lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 XRD spectra of (a) VO2 and (b) VS-0, VS-1, VS-2, and VS-3.

[0023] Figure 2 XPS spectrum of VS-2: (a) full spectrum; (b) Sn 3d; (c) V 2p; (d) O 1s.

[0024] Figure 3 SEM images of (a, b) VS-0, (c, d) VS-1, (e, f) VS-2, (g, h) VS-3, (i, j) VO2.

[0025] Figure 4 (a) TEM image of VS-2; (b) HRTEM image of VS-2; (c) elemental energy spectrum of VS-2. Figure 5 (a)VS-0 and (b)VS-2 at 0.01-3.0V (vs.Li / Li + ) Voltage range, 0.2Ag -1 Charge / discharge curves under current density conditions.

[0026] Figure 6 (a) VS-0, VS-1, VS-2, and VS-3 at a current density of 0.2A -1 Cyclic performance diagram under different conditions; (b) VS-0, VS-1, VS-2, VS-3 at current densities of 0.1, 0.2, 0.5, 1.0, 2.0, 0.1A respectively-1 (c) VS-2 at high current (0.5A) -1 ,1.0Ag -1 ,2.0Ag -1 ) conditions.

[0027] Figure 7 (a) VS-0 and (b) VS-2 at a scan rate of 0.1 mV s -1 Then get the CV graph.

[0028] Figure 8 (a) Electrochemical impedance spectroscopy (EIS) and (b) Warburg linear fitting diagram of VS-0, VS-1, VS-2, and VS-3. DETAILED DESCRIPTION

[0029] The present invention adopts a simple solvothermal method to synthesize a V-doped SnO2 composite material, and studies the effect of different V doping amounts on the electrochemical properties of the composite material. The results show that the suitable V-doped SnO2 sample (VS-2) has excellent electrochemical properties as a negative electrode active material for lithium-ion batteries.

[0030] The present invention is further described in detail below through implementation cases. This implementation case is implemented based on the technology of the present invention, and a detailed implementation method and specific operation process are now given to illustrate that the present invention is creative, but the protection scope of the present invention is not limited to the following implementation cases.

[0031] According to the information contained in this application, various changes can be easily made to the precise description of the present invention for those skilled in the art.It should be understood that the scope of the present invention is not limited to defined processes, properties or components, because these embodiments and other descriptions are only for illustrating specific aspects of the present invention.

[0032] In order to better understand the present invention but not to limit the scope of the present invention, all the numbers used in this application to express the amount, percentage, and other numerical values ​​should be understood as modified by the word "about" in all cases. Therefore, unless otherwise specified, the numerical parameters listed in the specification are approximate values, which may be changed according to the different ideal properties attempted to be obtained. Each numerical parameter should at least be regarded as obtained based on the reported significant figures and by conventional rounding methods.

[0033] The equipment and raw materials used in the present invention can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0034] Example

[0035] The present embodiment provides a method for preparing a V-doped SnO2 composite material, the method specifically comprising the following steps:

[0036] (1) VO2 was prepared by a simple hydrothermal reaction. Under magnetic stirring, oxalic acid dihydrate (0.6304 g, H2C2O42H2O) and ammonium metavanadate (0.5850 g, NH4VO3) were dissolved in 30 mL of deionized water. The yellow solution was then transferred to a 50 mL Teflon-lined reactor and heated in an oven at 180 °C for 48 h. After cooling to room temperature, the precipitate was separated by centrifugation and washed with deionized water and anhydrous ethanol. The VO2 powder was obtained by drying in a vacuum oven at 80 °C for 10 h.

[0037] (2) The V-doped SnO2 samples were synthesized by a typical solvothermal method. Stannous chloride (1 mmol, SnCl22H2O) and a certain amount of the above-synthesized VO2 were added to 30 mL of anhydrous ethanol and stirred for one hour. Finally, the precipitate was collected and washed with anhydrous ethanol and dried at 80 °C to obtain different V-doped SnO2 samples. According to the amount of VO2 added (0 mmol, 0.5 mmol, 1 mmol, 2 mmol), the four synthesized samples were marked as VS-0, VS-1, VS-2, and VS-3.

[0038] Structure and performance characterization:

[0039] The crystal structures of the synthesized samples were determined by X-ray diffractometer (XRD) (BrukerAxis, D8 diffractometer, Cu Kα radiation). The morphology of the compounds was observed by scanning electron microscopy (JEOL JSM-7100F, Japan). The elemental composition and element distribution of these samples were detected by X-ray photoelectron spectroscopy (XPS, ESCALAB 250XI) and transmission electron microscopy (TEM).

[0040] The button cells were assembled in an argon-filled glove box for subsequent testing of the electrochemical properties of the material. The synthesized sample was used as the active material, acetylene black was used as the conductive agent, and polyvinylidene fluoride (PVDF) was used as the binder. The three substances were uniformly mixed in a mass ratio of 7:2:1, and then N-methylpyrrolidone (NMP) was added dropwise to form a paste, which was scraped onto a copper foil and dried in a vacuum oven at 120°C for 10 hours. The copper foil was then cut into small discs with a diameter of 8 mm as the working electrode of the battery. A CR2025 button cell was assembled using a lithium sheet as the counter electrode, a Celgard 2300 diaphragm, and a nickel foam support, and an appropriate amount of electrolyte was dropped during the assembly process. The electrolyte was formed by dissolving 1 mol LiPF6 in 1L of a mixed solvent of diethyl carbonate / ethylene carbonate / dimethyl carbonate (volume ratio 1:1:1). The cycling and rate performance of the battery were tested on a land CT2001A battery tester. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) tests were performed on a CHI600E electrochemical workstation. All tests were performed at room temperature.

[0041] Results and discussion

[0042] Figure 1 a shows the XRD pattern of the synthesized VO2 powder. By comparing with the standard card JCPDS 71-0290, it can be seen that VO2 has been successfully synthesized. Figure 1 b shows the XRD patterns of VS-0, VS-1, VS-2 and VS-3. The characteristic peaks of VS-0 at 26.6°, 33.8°, 37.9° and 51.7° are consistent with those of tetragonal SnO2 (JCPDS 41-1445, P42 / mnm(136), ) and match the (110), (101), (200) and (211) crystal planes respectively. Figure 1 As shown, with V 4+ As the doping amount increases (from VS-1 to VS-3), the position of the SnO2 diffraction peak gradually shifts slightly to a larger angle. The reason for this result may be and The ionic radius of V 4+ Entering the tetragonal lattice and replacing Sn 4+ The position of V 4+ It was successfully doped into the SnO2 lattice. However, when the amount of V raw material used in the synthesis was greater than the amount of Sn, a VO2 peak was clearly seen in the synthesized sample (VS-3), indicating that the amount of V doped in VS-2 had reached its maximum value. 4+ The more V doped into the SnO2 lattice 4+The less there is, the more impurity peaks there are, which can be seen from Figure 1 This can be seen in the XRD spectrum of VS-3 in b.

[0043] Figure 2 It is the X-ray photoelectron spectroscopy (XPS) of VS-2 material. Figure 2 (a) shows the XPS total spectrum of VS-2. It can be clearly seen from the spectrum that the VS-2 sample contains V, Sn, O and C elements. Among them, the appearance of the C 1s peak is the result of using C during the XPS test process. Figure 2 (b, c, d) are the high-resolution XPS spectra of Sn 3d, V 2p and O1s, respectively. Two characteristic peaks at 494.55 and 486.10 eV can be observed from the Sn 3d spectrum, corresponding to Sn 3d3 / 2 and Sn 3d5 / 2 The distance between the two characteristic peaks is 8.45 eV, and the peak area ratio is 2:3, which is consistent with Sn 4+ -O three-dimensional binding energy data are consistent, indicating that the Sn element in the synthesized sample is only Sn 4+ Similarly, there are two characteristic peaks in the V 2p core energy spectrum, located at 523.70 and 516.45 eV, representing V 2p 1 / 2 and V 2p3 / 2 orbital. This indicates that the dopant is V 4+ The single peak in the O 1s core level spectrum can be fitted into two peaks at 529.80 and 531.35 eV, which are attributed to the lattice oxygen in VS-2 and the surface chemically adsorbed oxygen, respectively. In addition, through the analysis of XPS results, it can be calculated that the actual doping amount of V in VS-2 is about 41.67%, which is slightly lower than the designed content (50%).

[0044] like Figure 3 As shown in Figure 2, the microstructures of the four samples were obtained by scanning electron microscopy. Figure 3 From the scanning electron microscope images of pure SnO2 (VS-0) in (a, b), it can be seen that the undoped SnO2 is sub-bright in shape, with a size of about 500nm and accompanied by aggregation. When a certain amount of V dopant is added to SnO2, VS-1 and VS-2 are formed, and their morphologies are as follows: Figure 3 (c, d) and Figure 3 (e,f) After doping, the morphology and size of SnO2 changed significantly, becoming microspheres with a slightly rough surface and an average diameter of about 7μm. Although the doping amount was different, the morphology of VS-1 and VS-2 was almost the same. However, as the amount of dopant continued to increase, exceeding the V doping amount in SnO2 (VS-3), its morphology changed as shown in Figure 5. Figure 3As shown in (g,h), the shape is similar to popcorn. Compared with VS-1 and VS-2 samples, its surface is covered with many small particles, and the overall size has not changed significantly. In addition, a large number of nanoparticles are scattered or gathered around it. The morphology and size of the nanoparticles are the same as those of the previously prepared VO2 ( Figure 3 (i, j)), which also confirms the inference that the VO2 diffraction peak in XRD appears in VS-3. The above results show that vanadium doping has a certain effect on the morphology (including particle size) of SnO2, and the effect of doping amount on its morphology is different.

[0045] In order to further explore the microstructure and elemental composition of VS-2, we used transmission electron microscopy (TEM) to observe and analyze it. Figure 4 As shown. Figure 4 (a) It can be seen that the morphology of VS-2 is solid microspheres. Figure 4 (b)), it can be measured that the lattice fringe spacing is 0.26nm and 0.33nm, which corresponds to the (101) and (110) crystal planes of SnO2 respectively. Figure 4 (c)) once again proves the existence of the three elements Sn, V and O, which are evenly distributed in the microspheres.

[0046] Button cells were assembled using VS-0, VS-1, VS-2 and VS-3 as negative electrode materials for lithium-ion batteries, and their electrochemical performance was tested at a voltage of 0.01-3.0V. Figure 5 (a) and Figure 5 (b) VS-0 and VS-2 at a current density of 0.2A. -1 The charge and discharge curves of the first three cycles. Among them, the charging voltage platform range of VS-0 is 0.4-0.7V. The charge and discharge specific capacities of the first cycle are 1484mAh g -1 and 2271mAhg -1 , the Coulombic efficiency is 65.37%. In addition to the same low voltage platform (0.4-0.7V) as VS-0, the charging voltage platform of VS-2 is also increased to 1.1-1.4V, which is affected by the doped V 4+ The charge and discharge specific capacities of VS-2 in the first cycle were 1191 mAh g -1 and 1561mAhg -1 , the Coulombic efficiency is 76.30%, which is significantly higher than VS-0. Due to the partially reversible chemical reaction (SnO2+4Li + +4e -→Sn+2Li2O) and the formation of SEI film, the capacity dropped significantly from the first cycle to the second cycle. Although the initial charge and discharge capacity of undoped SnO2 (VS-0) is higher than that of V-doped SnO2 (VS-2), the capacity decay of VS-2 from the first cycle to the second cycle is much smaller than that of VS-0. The discharge specific capacity of VS-0 decayed by 727 mAh g -1 , while the discharge capacity of VS-2 only decayed by 334 mAh g -1 This may be because V 4+ The doping of SnO2 and Li + The reversible reaction slows down the formation of SEI film. In addition, due to the volume expansion of SnO2 during the cycle, it is easy to pulverize and agglomerate. The discharge capacity retention rate of VS-0 from the second cycle to the 100th cycle is only 23%, while the discharge capacity retention rate of VS-2 is as high as 87%. This shows that V 4+ The doping can effectively inhibit the volume change of SnO2 during the cycle and reduce the occurrence of electrode pulverization or agglomeration, thereby stabilizing the charge and discharge process.

[0047] The cycling performance of VS-0, VS-1, VS-2 and VS-3 was further tested and the results are as follows: Figure 6 (a) is shown. At 0.2Ag -1 At a current density of 1.34 W, VS-0 showed a very high initial discharge capacity (2271 mAh g -1 ), but then decayed rapidly, and at the 20th cycle, the specific capacity decayed to 931 mAh g -1 After 100 cycles, the discharge capacity is only 355 mAhg -1 . With the addition of V into SnO2 4+ As the amount of charge increases, the initial discharge capacity of VS-1 and VS-2 decreases, the discharge capacity decay from the first cycle to the second cycle also decreases, and the cycle stability within 100 cycles gradually improves. Therefore, after 100 cycles, the discharge capacity of VS-1 is still 762mAhg -1 , while the discharge capacity of VS-2 is as high as 1068 mAh g -1 However, although VS-3 has good cycling stability, its initial discharge specific capacity is low, only 1174 mAh g -1 , and the specific capacity from the first cycle to the second cycle also decreased significantly. After 100 cycles, the remaining specific capacity of VS-3 was only 579 mAh g -1 This may be due to the influence of VO2 in the samples, while the literature reports that the specific capacity of VO2 is lower. Therefore, among the four samples, VS-2 maintains the highest reversible capacity and the best cycling stability over 100 cycles.

[0048] The rate performance of the four samples was tested at different current densities. Figure 6 As can be seen in (b), VS-2 has a high current density of 0.1, 0.2, 0.5, 1.0 and 2.0Ag. -1 The discharge specific capacities were kept high, stabilizing at about 1249, 1066, 886, 734 and 484 mAh g -1 When the current density returns to 0.1A again -1 When it is charged, it can still reach 993mAhg -1 It can be seen that among the four samples, VS-2 has the best rate performance. Figure 6 (c) shows the current density of VS-2 at 0.5, 1.0 and 2.0A. -1 Cycling curves at . After 500 cycles, the discharge specific capacities of VS-2 at the corresponding current densities were 519, 280, and 258 mAh g-1, respectively. These results show that VS-2 has good cycling stability and high specific capacity even at high current densities, which once again demonstrates its excellent electrochemical performance.

[0049] Figure 7 (a) and Figure 7 (b) shows the cyclic voltammetry curves of VS-0 and VS-2, respectively. Figure 7 In (a), the reduction peak at 0.17 V in the first cycle voltammetry curve corresponds to Li x The formation of Sn (Sn+xLi + +xe - →Li x Sn(0≤x≤4.4)) and the formation of solid electrolyte interface (SEI). The reduction peak at 1.34V corresponds to the reduction of SnO2 (SnO2+4Li + +4e - →Sn+2Li2O). In the next few cycles, the two peaks shifted to 0.14V and 0.83V, respectively. Correspondingly, the oxidation peaks appeared at 0.58V, 1.24V, and 2.45V, corresponding to Li x Sn dealloying, Sn oxidation to SnO, SnO oxidation to SnO2. These three peaks did not shift significantly in the subsequent cycles. Compared with VS-0, VS-2 ( Figure 7 (b) The oxidation peak and reduction peak of V doping 4+ In the first cycle, except for the Li x In addition to the reduction peak corresponding to Sn formation and the reduction peak of SnO2 at 1.22V, there is also a peak at 0.79V corresponding to SEI film formation and V4+ Restore to V 3+ In the second cycle, the first two peaks move to 0.18V and 1.61V, respectively, V 4+ The reduction peak of 0.93 V is shifted. The position of the oxidation peak does not change much. 3+ The position of the oxidation peak is close to that of SnO2 oxidation peak, so both oxidation peaks appear on the broad peak at 2.49V.

[0050] In order to explore the reasons for the differences in electrochemical performance of the four samples, they were tested for electrochemical impedance spectroscopy (EIS) and fitted using relevant software. Figure 8 shown. Figure 8 (a) is the AC impedance curve of the four samples, and the upper left corner is the corresponding equivalent circuit diagram. In the equivalent circuit, R s Represents the electrolyte resistance, which is equivalent to the semicircular part in the high frequency region. C dl Represents the double layer capacitance at the interface between the electrode material and the electrolyte. R ct represents the charge transfer resistance from the electrode to the electrolyte. They both correspond to the semicircular part of the mid-frequency region. w is the Warburg impedance related to lithium ion diffusion, corresponding to the diagonal line in the low-frequency region. Figure 8 (b) shows the linear fit of the Warburg impedance. The slope of this curve in the low-frequency region is the Warburg coefficient (A w ). It is related to the lithium ion diffusion coefficient (D Li + ) is as follows

[39] :

[0051]

[0052] In the above formula, V m , F, S and dE / dx represent the molar volume of active materials, Faraday constant, electrode surface area, and open circuit voltage and Li in the electrode, respectively. + The slope of the tangent line of the concentration relationship curve. For the four samples, these parameters are the same and can be regarded as constants. Therefore, it can be inferred that D Li + With A w After simulation calculation, R s , R ct and A w The values ​​are shown in Table 1. The results show that the electrolyte resistance (R s ) is not much different, while the charge transfer resistance (R ct ) and the Warburg coefficient (A w ) are significantly different. Among the four electrodes, VS-2 has the highest R ct Value and A wThe values ​​of V-doped materials are the smallest, while VS-0 is the largest. That is, the V-doped material has a larger D Li + This means that the lithium ion transmission speed is faster. This shows that V doping improves the conductivity of the material and promotes the diffusion of lithium ions. This is also the reason why VS-2 has superior electrochemical performance.

[0053] Table 1 Fitting impedance data of VS-0, VS-1, VS-2, and VS-3

[0054]

[0055] In summary, the present invention synthesized SnO2 (VS-0) and SnO2 doped with V in different proportions (VS-1, VS-2, VS-3), and used them as negative electrode materials for lithium-ion batteries. Since VS-0 has a huge volume expansion during the cycle, the metal tin particles inevitably aggregate, so the cycle performance is poor and the capacity decays rapidly. However, the cycle stability of SnO2 doped with V has been significantly improved. In particular, when the doping ratio of V is 41.67%, its specific capacity retention performance and rate performance are optimal. At 0.2Ag -1 At a current density of 1.5 %, the specific discharge capacity can still be maintained at 1068 mAh g after 100 cycles. -1 In addition, even at high currents, it can maintain good cycle stability. -1 After 500 cycles at a current density of , the specific discharge capacities are stabilized at 519, 280 and 258 mAh g -1 All these demonstrate that V-doped SnO2 has excellent electrochemical properties and is a potential anode material for lithium-ion batteries.

Claims

1. A method for preparing a V-doped SnO2 composite material, characterized in that: The method specifically comprises the following steps: The stannous salt is dissolved in anhydrous ethanol, and then vanadium dioxide (VO2) is added according to a proportion and mixed; the obtained mixed reaction liquid is reacted at room temperature under stirring conditions for 1 hour; after the reaction is completed, the reaction product is collected, washed and dried to obtain the V-doped SnO2 composite material.

2. The preparation method according to claim 1, characterized in that: The stannous salt is stannous chloride or stannous sulfate.

3. The preparation method according to claim 1, characterized in that: The usage ratio of the stannous salt to anhydrous ethanol is 1 mmol:30 mL.

4. The preparation method according to claim 1, characterized in that: The molar ratio of the vanadium dioxide to the stannous salt is (0.5-2):

1.

5. The preparation method according to claim 1, characterized in that: The vanadium dioxide is synthesized by a hydrothermal method, and the specific steps are as follows: Oxalic acid and ammonium metavanadate are dissolved in deionized water in turn according to the ratio, and then the obtained yellow solution is transferred to a high-pressure reactor, heated to 180° C. and reacted at a constant temperature for 48 hours; after the reaction is completed, the product is cooled to room temperature, centrifuged to separate the precipitate, washed, and dried to obtain the vanadium dioxide.

6. The preparation method according to claim 5, characterized in that: The molar ratio of the oxalic acid to the ammonium metavanadate is 1:

1.

7. The preparation method according to claim 5, characterized in that: The usage ratio of the ammonium metavanadate to deionized water is 5 mmol:30 mL.

8. The V-doped SnO2 composite material prepared by the method according to any one of claims 1 to 7.

9. Use of the V-doped SnO2 composite material prepared by the method according to any one of claims 1 to 7 as a negative electrode active material in a lithium-ion battery.

10. A lithium ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The active material used in the negative electrode is a V-doped SnO2 composite material prepared by the method according to any one of claims 1 to 7.